2026 Renewals in University Community Work Projects, Western Campus - Alfaro Rodríguez, Arelys (2026)
This article analyzes the 2026 renewal formulations of seven University Community Work (TCU) projects at the Western Campus of the University of Costa Rica (UCR), in the context of the 50th anniversary of this Social Action modality. The central problem guiding the study is the identification of strengths and opportunities for improvement in the renewal formulation processes, in light of current regulations, particularly circulars VAS-29-2021 and VAS-14-2025. Through an analytical-qualitative approach combining documentary analysis and semi-structured interviews, categories such as planning, articulation, social relevance, methodological clarity, social action principles, institutional relevance, and evaluation are examined. Findings reveal common patterns in strengths—such as congruence between objectives and activities—and in opportunities for improvement—especially regarding the explicit incorporation of the community work protocol and evaluative depth. The article has a propositional character: based on the analysis, concrete strategies are offered to strengthen the formulation and renewal processes of TCU projects.